Precision Product-Process Design and Optimization Select Papers from AIMTDR 2016 (Lecture Notes on Multidisciplinary Industrial Engineering,, 2018)
This book introduces readers to various tools and techniques for the design of precision, miniature products, assemblies and associated manufacturing processes. In particular, it focuses on precision mechanisms, robotic devices and their control strategies, together with case studies. In the context of manufacturing process, the book highlights micro/nano machining/forming processes using non-conventional energy sources such as lasers, EDM (electro-discharge machining), ECM (electrochemical machining), etc. Techniques for achieving optimum performance in process modeling, simulation and optimization are presented. The applications of various research tools such as FEM (finite element method), neural networks, genetic algorithms, etc. to product-process design and optimization are illustrated through case studies. The state-of-the-art material presented here provides valuable directions for product development and future research work in this area. The contents of this book will be of use to researchers and industry professionals alike.